Microsponge: An Advanced Drug Delivery System - Rakholiya, Swati; Dutta, Disha; Gupta, Shiv Kumar (Current Applied Polymer Science, 2023)
Porous microsponges are a type of polymeric delivery method. These tiny, spherical particles, resembling sponges, have a large porous surface, which helps to modify drug release, stabilize the substance, and lessen side effects. To keep dose forms on the skin, micro sponges can be successfully included intopical medicine administration systems. Since the outer surface is frequently porous, the material can continuously flow out of the sphere. This system can suspend or entrap a variety of substances, and it can be incorporated into a manufactured product like a liquid, gel, cream, or powder. The majority of vehicles and components can be used with these formulations, which are stable in the pH range of 1 to 11 and up to 130ºC. Microsponges are created to reduce side effects, change medication release, and enhance stability to successfully distribute a pharmaceutically active component at the lowest amount achievable.
Keywords: controlled release